Compomers in restorative therapy of children: a literature review - NORBERT KRÄMER, & ROLAND FRANKENBERGER (IAPD and Blackwell, 2007)
The restoration of carious primary teeth plays an underestimated role in paediatric dentistry. This is astonishing for many reasons, not least because many new materials have been introduced in recent years.